The Chronicles of Count Antonio - Hope, Anthony, 1863-1933; Van Schaick, S. W. (Stephen Wilson), 1850?-1920 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Chronicles of Count Antonio" by Anthony Hope is a historical novel written in the late 19th century. It follows Count Antonio of Monte Velluto, who becomes an outlaw after defying Duke Valentine, the ruler of Firmola, in a quest for love and justice. The narrative weaves themes of loyalty, rebellion, and the intertwining of romantic love with political intrigue. At the start of the novel, Count Antonio approaches Duke Valentine to seek permission to marry Lady Lucia, a ward of the Duke. However, the Duke has other plans, promising the lady to a favored suitor, Lord Robert de Beauregard. Defiant and deeply in love, Antonio's rejection of the Duke's authority sets off a chain of events that lead to his outlaw status. The opening chapters establish a tense atmosphere filled with political manipulation, personal betrayal, and foreshadow a gripping conflict as Antonio, fueled by love and loyalty, prepares to confront the Duke's tyranny. (This is an automatically generated summary.)
Release date is 2012-08-23
E-text prepared by Suzanne Shell, Mary Meehan, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://archive.org/details/americana)
Keywords: Love stories; Italy -- Fiction; Adventure stories; Nobility -- Fiction; Outlaws -- Fiction